THE IMPACT OF TQM PRACTICES ON FACULTY TEACHING PERFORMANCE IN PALESTINIAN WEST BANK UNIVERSITIES: MEDIATOR ROLE OF HYBRID TEACHING METHODS - Omar, Sara (An-Najah National University, 2024)
The institutions of Palestinian higher education have an essential and important role in promoting intellectual development, shaping national identity, and contributing to social progress despite the challenges arising from the ongoing Israeli-Palestinian conflict. In the past few years, Palestinian higher education institutions have moved towards a blended education policy due to the restrictions imposed by the Israeli occupation that limit traditional educational practices. Also, effective teaching is the foundation of any higher education system, and implementing Total Quality Management (TQM) practices emerges as an effective strategy to enhance teaching performance. Therefore, the aim of this study is to examine the relationship between blended teaching methods and Total Quality Management (TQM) practices, specifically their impact on faculty teaching performance in Palestinian higher education. Additionally, the study will explore whether blended teaching methods serve as a mediator in this relationship. Using the quantitative approach in this study, the necessary data was collected by distributing 82 questionnaires on faculty members across different Palestinian universities. The collected data was then analyzed using the Smart PLS program to test the hypotheses. The results showed that there is a positive and high relationship between total quality management practices and both the teaching performance of faculty members and blended teaching methods. Additionally, the findings support the positive relationship between TQM practices and both faculty teaching performance and blended teaching methods. However, the effect of blended teaching methods on the faculty teaching performance is not significant and blended teaching methods has no mediating role in this relationship. And as a conclusion of this study, it indicates that the higher educational institution’s role is critical and important to improve the relationship between the adoption of TQM practices, blended teaching methods and faculty teaching performance. This study also found that the adoption of blended teaching methods in Palestinian higher education faces limitations relate to both faculty perceptions and institutional challenges that prevent it from mediating the relationship between total quality management practices and the teaching performance of faculty members. However, we believe that the results of this research may be useful to decision makers in Palestinian higher education institution in order to make appropriate decisions and improve the educational institutions strategies to encourage the use of blended teaching methods.
أثر ممارسات إدارة الجودة الشاملة على الأداء التدريسي لأعضاء هيئة التدريس في جامعات الضفة الغربية الفلسطينية: الدور الوسيط لطرق التدريس الهجينة